Modification Of Bismuth Ferrite Through Calcium- And Copper-Doping For Enhanced Antibiotics Removal Via Catalytic Peroxymonosulfate Activation - Koo, Pooi Ling (2023)
The main objective of this research is to improve the catalytic activity of Bi2Fe4O9 through doping for the removal of fluoroquinolone antibiotics via PMS activation.